(untitled) (Bangladesh Journal of Medical Microbiology, 2020)
Genetically inherited characteristics of blood group phenotypes, whose association with certain infectious diseases have been debated for long. Growing evidence suggests that ABO blood group may play a role in the immunopathogenesis of SARS-CoV-2 infection. The level of evidence supporting an association between ABO type and COVID-19 ranges from small observational studies, to genome-wide-association-analyses and country-level meta-regression analyses. We tried to find out the molecular relations of SARS-CoV-2 infection and ABO blood groups. We discussed inherited associations and possible molecular mechanisms that drive the relationship between blood type and COVID-19. Similar and non-similar comments and demonstrations from several studies are simply notified here. Bangladesh J Med Microbiol 2020; 14 (2): 30-35